Performance Analysis of Space-Time Block Coded MIMO System With Channel Estimation Error in Different Fading Channels - Goyal, Nidhi (My University, 2008)
Wireless communication is a rapidly growing segment of the communication industry, with the potential to provide high-speed, high-quality information exchange between portable devices located anywhere in the world. Wireless communication is the transfer of information over a distance without the use of electrical conductors or "wires". The distances involved may be short (a few meters as in television remote control) or very long (thousands or even millions of kilometers for radio communications). For long distance communication, wireless systems are working on Multiple-Input–Multiple Output (MIMO) antenna technology now a days. It has recently emerged as one of the most significant technical breakthroughs in modern communications. The technology figures prominently on the list of recent technical advances with a chance of resolving the bottleneck of traffic capacity in future internet-intensive wireless networks. MIMO is an antenna technology for wireless communications in which multiple antennas are used at both the source (transmitter) and the destination (receiver). The antennas at each end of the communications circuit are combined to minimize errors and optimize data speed. MIMO is one of several forms of smart antenna technology. MIMO systems use Space–Time Block Coding (STBC) coding technique. Space–Time Block Coding (STBC) is an attractive solution to improve the quality of wireless links. Space–Time Block Coding is a technique used in wireless communications to transmit multiple copies of a data stream across a number of antennas and to exploit the various received versions of the data to improve the reliability of data-transfer. The fact that the transmitted signal must traverse a potentially difficult environment with scattering, reflection, refraction and then further corrupted by thermal noise in the receiver. It means that some of the received copies of the data will be better than others. Space–Time Coding combines all the copies of the received signal in an optimal way to extract as much information from each of them as possible. Shannon Capacity and Symbol Error Rate (SER) are two measures which describes systems quality. It is the channel which effects the transmission in wireless communication. Mostly, the noise components are present in channel. In the present work an attempt has been made to study the impact of channel estimation error on Ergodic Capacity and Bit Error Rate (BER) for Space–Time Block Coded Multiple-Input Multiple-Output systems. MATLAB is used for simulation of the study. Shannon Capacity analysis is done in different fading environments namely Rayleigh, Rician and Nakagami fading channels with different channel errors. Ergodic capacity ratio and outage probability analysis is also done in Rayleigh fading environment. Error probability analyses of orthogonal space-time block coded MIMO system is analyzed for pulse-amplitude modulation/phase shift keying/quadrature-amplitude modulation (PAM/PSK/QAM) in different fading channels with channel estimation error. The study reveals that as the channel error approaches to ‘one’ system approaches to be ideal. With the increase in number of transmit and receive antennas, the sensitivity of the STBC system to channel estimation error increases. In different fading channels, Nakagami fading channel gives best ergodic capacity. In BER analysis, among all modulation techniques (QPSK, PAM, and QAM) the BER of QPSK is least. Among all the fading channels, Nakagami fading channel gives the best performance as compared to others fading channels. In Nakagami fading environment ergodic capacity is highest and symbol error is least for different modulation techniques.
M.E. (ECED)
Keywords: wireless communication